2009
DOI: 10.1007/s10787-009-8049-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (cox-2) blockade in the chemoprevention of cancers of the colon, breast, prostate, and lung

Abstract: The existing epidemiologic literature was comprehensively reviewed to retrieve all epidemiologic studies (case control and cohort studies) that examined exposure to traditional over the counter nonsteroidal anti-inflammatory drugs (OTC NSAIDs) and the risk of cancers of the colon, breast, prostate and lung from 1980 forward. These malignancies account for more that half of all cancer deaths in the United States and the United Kingdom. Estimates of effects (relative risks or odds ratios) and 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
218
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(234 citation statements)
references
References 184 publications
3
218
0
7
Order By: Relevance
“…11,53 As a result of documented cardiovascular side effects of COX-2 inhibitors, 25,26,54 alternative and safer therapies as single agent or in combination (as adjuvant) need to be tested in preclinical models. Based on our earlier data on the role of EP4 in multiple cellular events promoting breast cancer progression, our present preclinical data, and the fact that EP4 may have some redundancy for physiological functions shared with EP2, we suggest that EP4 may prove to be a safe target in the clinic for preventing and mitigating lymphatic metastasis of breast cancer in combination with other agents.…”
Section: Therapy With Cox-1/2 Inhibitor Cox-2 Inhibitor or Ep4 Antagmentioning
confidence: 99%
“…11,53 As a result of documented cardiovascular side effects of COX-2 inhibitors, 25,26,54 alternative and safer therapies as single agent or in combination (as adjuvant) need to be tested in preclinical models. Based on our earlier data on the role of EP4 in multiple cellular events promoting breast cancer progression, our present preclinical data, and the fact that EP4 may have some redundancy for physiological functions shared with EP2, we suggest that EP4 may prove to be a safe target in the clinic for preventing and mitigating lymphatic metastasis of breast cancer in combination with other agents.…”
Section: Therapy With Cox-1/2 Inhibitor Cox-2 Inhibitor or Ep4 Antagmentioning
confidence: 99%
“…Our current study revealed that COX-2 methylation was decreased in H. pylori-positive subjects after two-year lowdose (200 mg twice daily) intake of celecoxib. Although the mechanism of COX-2 methylation reduction by celecoxib still remains unclear, it may primarily involve the down-regulation of inflammatory reaction by direct COX-2 activity inhibition and the subsequent reduction of catalyzed prostaglandins or cytokines even in subjects with H. pylori remained in the gastric epithelial (36). A more significant decreasing trend of COX-2 methylation by celecoxib in chronic atrophic gastritis rather than in intestinal metaplasia might be resulted from the more significant prevalence of chronic inflammation in chronic atrophic gastritis than in intestinal metaplasia lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases involve inlammatory responses either as a reaction to disease or in the initiation of the disease process; although inlammation itself is not always detrimental, for instance, it is an important aspect of wound repair [11][12][13][14]. Elevated markers of inlammation are frequently detected in heart failure and cancers although this could be due to the response to disease, or the underlying cause of disease [15][16][17][18][19].…”
Section: Inlammation Disease and The Immune Systemmentioning
confidence: 99%